2020
DOI: 10.3390/cancers12103067
|View full text |Cite
|
Sign up to set email alerts
|

Therapy Resistance, Cancer Stem Cells and ECM in Cancer: The Matrix Reloaded

Abstract: The extracellular matrix (ECM) has remained an enigmatic component of the tumor microenvironment. It drives metastasis via its interaction with the integrin signaling pathway, contributes to tumor progression and confers therapy resistance by providing a physical barrier around the tumor. The complexity of the ECM lies in its heterogeneous composition and complex glycosylation that can provide a support matrix as well as trigger oncogenic signaling pathways by interacting with the tumor cells. In this review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 125 publications
(160 reference statements)
0
40
0
Order By: Relevance
“…However, we observe a significant decrease in the Ki-67 staining in vivo tumors formed by biglycan-negative cells. Furthermore, in the in vivo context, tumors formed by biglycan-negative cells lead to a decrease of the ECM cohesive phenotype that can be associated with a decrease cancer cell survival [ 53 ]. In fact, Andrlová et al [ 25 ] described that biglycan is able to modulate ECM organization/structure by up-regulating the expression of the integrin-β1 adhesion molecule, which, in turn, increases the matrix stiffness and modulates the tumor-related survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, we observe a significant decrease in the Ki-67 staining in vivo tumors formed by biglycan-negative cells. Furthermore, in the in vivo context, tumors formed by biglycan-negative cells lead to a decrease of the ECM cohesive phenotype that can be associated with a decrease cancer cell survival [ 53 ]. In fact, Andrlová et al [ 25 ] described that biglycan is able to modulate ECM organization/structure by up-regulating the expression of the integrin-β1 adhesion molecule, which, in turn, increases the matrix stiffness and modulates the tumor-related survival.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, genomic and transcriptomic analysis have demonstrated that the activated gene sets in response to TGF-β signaling are involved in regulating various pathophysiological processes including EMT, wound healing, angiogenesis, and dissemination ( Hugo et al, 2016 ). On the other hand, TGF-β can regulate immune response by orchestrating the crosstalk of multiple cell types in the TME, including CAFs, lymphocytes, and endothelial cells ( Korneev et al, 2017 ; Chakravarthy et al, 2018 ; Kesh et al, 2020 ). TGF-β can inhibit the proliferation and differentiation of anti-tumor T cells by increasing the expression of CD25 and Foxp3 ( Löffek, 2018 ).…”
Section: Tme-driven Adaptive Mechanisms Of Therapy Resistancementioning
confidence: 99%
“…The ECM in breast tumors is integral to the invasion and metastasis of BC. In recent years, increasing evidence has indicated that the ECM may also play an important role in mediating resistance to existing treatments (77)(78)(79). It provides an adhesion matrix and specific matrix components that promote survival mechanisms to support and induce stem cell pathways and enhance cell metastasis and invasion (80).…”
Section: Treatment Resistance Induced By Ecmmentioning
confidence: 99%